Introduction to psychology : gateways to mind and behavior - Coon, Dennis; Mitterer, John O. (Wadsworth, Cengage Learning, 2009)
Integrates the proven-effective SQ4R learning system (Survey, Question, Read, Reflect, Review, Recite), which promotes critical thinking as it guides students step-by-step to an understanding of psychology's broad concepts and diversity of topics.